FROM FRAMING TO FLAMING IN THE CROSS-THEOLOGICAL DEBATE: HOW ARE CHRISTIAN PRINCE’S COMMENTARIES REPRESENTED THE QUR’AN ON YOUTUBE? - Amir, Abdul Muiz; Wahidah, Fatira; Zakir, Muhammad; Ainurrofiq, Faiq (Islam Futura, 2023)
Christian Prince’s (CP) presence on YouTube opened a new chapter in Christian opposition actors who act as cross-theological debaters between Muslims and Christians who, for the previous two decades, were only dominated by Muslims. Through the narratives on YouTube, this Christian apologist tries to convince the public that the Qur’an contains contradictory statements as the holy book for Muslims. In response to such an issue, this research aims to investigate the construction of CP’s interpretation, which highlights the authenticity of the Qur’an. Qualitative content and thematic analyses and the framing approach developed by William A. Gamson were employed. Findings suggest that the representation of CP’s understanding of the Qur’an verses uses a decontextualization approach. Also, the vast knowledge of the Arabic language and literary translations further strengthen the narratives to convince the public of the allegations. However, instead of considering the historical context in understanding the scientific meaning of the Qur’an, this Christian apologist uses literal meaning as a framing device. This phenomenon has shown that cross-theological debates only provoke persistent inter-religious hatred and resentment. Therefore, such debates are inclined to trigger the propaganda of religious extremists.